Innovative use of a self-expanding valve for valve-in-valve transcatheter mitral valve replacement: experience from a four-year single-center study - Li, Yuehuan; Lei, Ruobing; Zhou, Jiawei; Wu, Kaisheng; Shen, Jinglun; Zhu, Zhihui; Wang, Jiangang; Zhang, Haibo (Frontiers in Cardiovascular Medicine, 2023)
Background Valve-in-valve transcatheter mitral valve replacement (ViV-TMVR) is a minimally invasive option for patients with bioprosthetic mitral valve failure. Since January 2019, our center has been using a new innovative option, J-Valve, to treat patients with bioprosthetic mitral valve failure who were at high risk for open heart surgery. The aim of this study is to explore the effectiveness and safety of J-Valve and report the results from the four-year follow-up period of the innovative application of the transcatheter valve. Methods Patients who underwent the ViV-TMVR procedure between January 2019 and September 2022 in our center were included in the study. J-Valve™ system (JC Medical Inc., Suzhou, China) with three U-shape grippers was used for ViV-TMVR via transapical approach. Data on survival, complications, transthoracic echocardiographic results, New York Heart Association functional class in heart failure, and patient-reported health-related quality of life according to the Kansas City Cardiomyopathy Questionnaire-12 (KCCQ-12) were collected during the four-year follow up. Results Thirty-three patients (mean age 70.1 ± 1.1 years, 13 men) were included and received ViV-TMVR. The surgery success rate was 97%: only one patient was converted to open-heart surgery due to intraoperative valve embolization to the left ventricle. During the first 30 days all-cause mortality was 0%, risk of stroke 2.5% and risk of mild paravalvular leak 15.2%; mitral valve hemodynamics improved (179.7 ± 8.9 at 30 days vs. 269 ± 49 cm/s at baseline, p < 0.0001). Median time from operation to discharge was six days, and there were no readmissions within 30 days from operation. The median and maximum follow-up durations were 28 and 47 months, respectively; during the entire follow-up, all-cause mortality was 6.1%, and the risk of cerebral infarction 6.1%. Cox regression analysis did not identify any variables significantly associated with survival. The New York Heart Association functional class and the KCCQ-12 score improved significantly compared with their preoperative values. Conclusion The use of J-Valve for ViV-TMVR is safe and effective with a high success rate, low mortality and very few associated complications, representing an alternative surgical strategy for the elderly, high-risk patients with bioprosthetic mitral valve failure.